The Relationship Of Emotional Intelligence To The Performance Of Teachers Of Physical Education And Sports - Kermiche, A.malek Farid (sports creativity, 2025)
This study aimed to investigate the relationship between emotional intelligence and performance among physical education teachers. The researcher employed a descriptive methodology, deemed most suitable for the study's subject matter. The sample consisted of 64 physical education teachers working in middle schools in the city of M'Sila. The researcher utilized both an emotional intelligence scale and a physical education teachers' performance evaluation questionnaire. Key findings include: - A strong correlation exists between self-awareness (emotional knowledge), a component of emotional intelligence, and performance among physical education teachers. - A strong correlation exists between emotional regulation, a component of emotional intelligence, and performance among physical education teachers. - A strong correlation exists between emotional management, a component of emotional intelligence, and performance among physical education teachers. - A strong correlation exists between empathy, a component of emotional intelligence, and performance among physical education teachers. There is a strong correlation between social interaction, as a component of emotional intelligence, and the performance of physical education teachers. There is also a strong correlation between elements of emotional intelligence in general and the performance of physical education teachers. Therefore, emotional intelligence is considered one of the most important and essential factors for physical education teachers to excel and succeed in the educational field.